Are Poverty Reduction Strategy Papers Associated with Reductions in Poverty and Improvements in Well-being?. Issue 2 (1st February 2018) - Elkins, Meg; Feeny, Simon; Prentice, David
Abstract: Should Poverty Reduction Strategy Papers (PRSPs) be the tool for implementing the new Sustainable Development Goals, as they were for the Millennium Development Goals? Surprisingly, despite the controversies around them, there has never been a quantitative evaluation of PRSPs. This paper estimates the impact of having a PRSP on various targets of the Millennium Development Goals. Results suggest that countries under PRSP treatment achieve much greater reductions than control countries, in head count poverty and infant mortality, while also achieving greater improvements in primary school enrolments and gender parity.